Attitudes to the use of Google Translate for L2 production: analysis of chatroom discussions among UK secondary school students. Issue 3 (4th May 2023) - Organ, Alison
ABSTRACT: This paper presents the findings of a research project on UK school students' attitudes to the use of Free Online Machine Translation for L2 production and more specifically in preparing for assessment. Data were collected from a publicly available online forum to analyse students' spontaneous discussion of the use of Free Online Machine Translation, predominantly Google Translate. The majority of relevant comments were posted by secondary school students in the UK, regarding the use of Google Translate for GCSE examinations. The findings reveal that use of Google Translate for assignments was accepted practice among secondary school students in the UK over the last decade. However, they show mixed attitudes to this usage, and the nature of the discussion changed over the decade as a result of the evolution of Google Translate and changes to UK examination requirements. This study is original in its use of netnography, the study of online communities, to analyse students' comments to each other about their use of Google Translate in preparing for modern foreign languages (MFL) coursework. These findings, therefore, serve to inform the debate on how schools and universities should respond to student Google Translate usage for language learning and assignments.